Functional Status After Colon Cancer Surgery In Elder Nursing Home Residents - Finlayson, Emily (J Am Geriatr Soc, 2012)
OBJECTIVES: To determine functional status and mortality rates after colon cancer surgery in older nursing home residents. DESIGN: Retrospective cohort study. SETTING AND PARTICIPANTS: 6822 nursing home residents age 65 and older who underwent surgery for colon cancer in the United States between 1999 and 2005. MEASUREMENTS: Changes in functional status were assessed before and after surgery using the Minimum Data Set-Activities of Daily Living (MDS-ADL) summary scale, a 28-point scale in which score increases as functional dependence increases. METHODS: Using the Medicare Inpatient File and the Minimum Data Set for Nursing Homes, we identified the 6822 nursing home residents age 65 and older who underwent surgery for colon cancer. We used regression techniques to identify patient characteristics associated with mortality and functional decline at 1 year after surgery. RESULTS: On average, residents who underwent colectomy experienced a 3.9 point worsening in MDS-ADL score at one year. One year after surgery, the rates of mortality and sustained functional decline were 53% and 24%, respectively. In multivariate analysis, older age (age 80+ v. age 65–69, adjusted relative risk (ARR 1.53), 95%CI 1.15–2.04, p<0.001), readmission after surgical hospitalization (ARR 1.15), 95%CI 1.03–1.29, p<0.01), surgical complications (ARR 1.11), 95%CI 1.02–1.21, p<0.02), and functional decline before surgery (ARR 1.21, 95%CI 1.11–1.32, p<0.0001) were associated with functional decline at one year. CONCLUSION: Mortality and sustained functional decline are very common after colon cancer surgery in nursing home residents. Initiatives aimed at improving surgical outcomes are needed in this vulnerable population.